Distributions of Cu and Zn in the shell lipped part periostracum and soft tissues of perna viridis: the potential of periostracum as a biomonitoring material for Cu contamination - Yap, Chee Kong (Universiti Putra Malaysia Press, 2012)
Periostracum is the outer shell layer composes mainly of organic materials. In the present study, the green-lipped mussel Perna viridis was used to investigate the distributions of Cu and Zn in the periostracum and soft tissues of the P. viridis which were sampled from 17 geographical sites [23 populations] along the coastal waters of Peninsular Malaysia. The concentrations of Cu in the periostracum and the soft tissues of P. viridis were 7.41- 42.63 mg/g dry weight and 3.49-31.1 mg/g dry weight, respectively. Meanwhile, the concentrations of Zn in the periostracum and soft tissues of P. viridis were 4.90-39.79 mg/g dry weight and 65.75-144.9 mg/g dry weight, respectively. The ratios of the metals in periostracum to soft tissues were 0.73-3.99 mg/g for Cu and 0.05-0.36 mg/g for Zn. These ratios indicated that the concentrations of Cu in the periostracum were generally greater than those in the soft tissues while the concentrations of Zn were generally higher in the soft tissues than those in the periostracum. The higher Cu levels in the soft tissues compared to that in the periostracum (Fig. 2) and the relatively close relationships of Cu between periostracum and sediment indicated that the periostracum was a good biomonitoring material for Cu, but periostracum was not a good biomonitoring material for Zn because it did not reflect the environmental contamination as reflected in the low correlation between the periostracum and sediment.